Use of face masks to limit the spread of the COVID-19 among western Ugandans: Knowledge, attitude and practices. - Franck Katembo Sikakulya; Robinson Ssebuufu; Simon Binezero Mambo; Theophilus Pius; Annet Kabanyoro; Elizabeth Kamahoro; Yusuf Mulumba; Jean Kakule Muhongya; Patrick Kyamanywa (PLoS ONE, 2021)
Background The world is grappling with an ever-changing COVID-19 pandemic using preventive measures such as personal hygiene, face masks, restrictions on travel and gatherings in communities, in addition to a race to find a vaccine. The purpose of this study was to evaluate the knowledge, attitudes and practices of the western Uganda community on the proper use of face masks to mitigate the spread of COVID-19. Methods A cross-sectional study using a structured questionnaire was carried out from 1st July to 10th July 2020 among western Ugandans of consent age of 18 years and above. Data was analysed using Stata version 14.2. Results Among the respondents (n = 1114), the mean age was 30.7 (SD 11.1), 51% were males, 53.9% married and 43% had attained secondary education. Most participants (60.1%, n = 670) had satisfactory knowledge on the use of face masks and participants at a tertiary education level [AOR 2.6 (95% CI: 1.42-4.67; p = 0.002)] were likely to have satisfactory knowledge than participants who had not education. On attitude, most respondents (69.4%) were confident enough to correctly put on a face mask; 83.4% believed that a face mask can protect against COVID-19 and 75.9% of respondents had never shared their face mask. The majority of respondents (95.2%) agreed wearing face masks in public places was important to protect themselves against COVID-19; 60.3% reported washing their hands before wearing and after removing the face mask. Unfortunately, 51.5% reported removing the face mask if they needed to talk to someone. Conclusion Despite the satisfactory knowledge, good attitude and practices, there is still much more to be done in terms of knowledge, attitude and practices among participants. Government, non-governmental organizations and civil society should improve sensitization of populations on how to behave with face masks while talking to avoid the spread of the COVID-19 among western Ugandans.